An observational study to compare Muhtaseb’s and Habib’s scoring systems in patients undergoing phacoemulsification to predict risk in cataract at a tertiary centre in West Bengal - Singh, Jagan Nandan Prasad; Biswas, Atanu (International Journal of Research in Medical Sciences, 2023)
Background: Cataract is derived from the Latin ‘cataracta’, meaning ‘waterfall’ as rapidly running water turns white, so term may have been used metaphorically to describe similar appearance of mature ocular opacities.1 Methods: This observational study with prospective study design has been conducted in the college of medicine and JNM hospital, department of ophthalmology, COMJNMH, Kalyani-741235, Nadia District, West Bengal which catering mostly the rural and also urban population. The study was done spread over a period of 18 months starting from July 2018 to December 2019, i.e., 1 year for research and 6 months for analysis. It included all patients, irrespective of age, undergoing Phacoemulsification surgery for cataract admitted in our hospital fulfilling the laid criteria for the study. Results: The study consisted of total 147 cases in these 14 (9.52%) cases complicated with PCR, 10 (6.80%) striate keratopathy and 4 (2.72%) cases complicated with both PCR and striate keratopathy. Though sample size derived was 126 cases, 147 cases were studied during the research period of 1 year. Out of 10.89% cases of miscellaneous risk (ex: poor position of the eye/patient) risk factor, posterior capsule rupture (12.5%), striate keratopathy (12.5%), cases having both complication (00.0%) and total complicated cases (25%) which is 1.36%, 1.36%, 0% and 2.72% of total cases respectively. Out of 8.84% cases of unable to lie flat risk factor, posterior capsule rupture (15.38%), striate keratopathy (7.69%), and total complicated cases (23.07%) which is 1.36%, 0.68% and 2.04% of total cases respectively. Conclusions: The current study tries to validate two scoring systems to predict complications during phacoemulsification surgerylike risk of posterior capsule rupture and striate keratopathy and to predict the potential difficulty of a case.